The Impact of Nursing Service Quality on Length of Hospital Stay in Children with Pneumonia: A Literature Review - Gloria Angelika Waruwu; Angela Meicilia; Permaida Permaida; Mariam Dasat (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Pneumonia is one of the serious diseases that occurs in the lower respiratory tract. This disease is one of the causes of death among children, especially those under five years of age. This condition is of great concern to health workers, especially nurses, because proper treatment can help reduce mortality rates. Therefore, quality and comprehensive nursing care is needed so that the healing process runs optimally. This study aims to determine how the quality of nursing care can affect the length of hospital stay in children with pneumonia. Method: This study used a literature review approach by searching Google Scholar for publications from 2020 to 2025. The keywords used were “children with pneumonia,” “nursing care,” “length of stay,” and synonyms such as “pneumonia in children,” “quality of nursing care for children,” and “duration of hospitalization.” Result: Six articles that met the inclusion criteria were found. The analysis showed that 83.3% (n=5) of these articles proved that the quality of nursing care had an effect on reducing the length of hospital stay, while 16.7% (n=1) of the articles highlighted the importance of a non-pharmacological approach to reducing children's anxiety during treatment. Nurses play a central role in every stage of nursing care, from observation, education, and therapy to interprofessional collaboration. Conclusion: These findings confirm that comprehensive nursing care focused on children's needs can accelerate the healing process and reduce the length of hospital stays. Therefore, the quality of nursing care needs to be continuously improved in order to have a positive impact on the quality of life and safety of pediatric patients in healthcare facilities.